The impact of a vaccine scare on parental views, trust and information needs: a qualitative study in Sydney, Australia - Catherine King; Julie Leask (BMC, 2017)
Abstract Background Vaccine safety scares can undermine public confidence in vaccines and decrease immunisation rates. Understanding and addressing parental concerns arising during such scares can assist in lessening their impact. In Australia in April 2010 there was a temporary suspension of influenza vaccine for children under 5 years of age after reports of an increase in the rate of adverse events following vaccination. This qualitative study aimed to explore the impact of the vaccine suspension on parental knowledge, attitudes, trust, information needs, and intent related to influenza vaccination and broader immunisation programs. Methods Semi-structured interviews were conducted with 25 parents of children attending childcare centres in Sydney, Australia, between June 2010 and May 2011. Centres were selected to include parents from a range of socioeconomic backgrounds. Interview transcripts were coded and analysed using an approach informed by grounded theory. Results Findings indicated that, for those who recalled the vaccine suspension, there was a lasting sense of uncertainty and confusion and a perceived lack of information. Parents had distinct information needs following the vaccine suspension, especially in regards to vaccine safety, testing and recommendations. For many, influenza vaccination intent was conditional on receipt of information from a trusted, authoritative source allaying safety concerns. Importantly, the impact of the scare was contained to influenza vaccines only, and not other vaccine programs. Conclusions Parental concerns and information gaps following a vaccine safety scare need to be actively addressed. We provide policy and practice suggestions for proactively managing such incidents, particularly in relation to communication of timely, targeted information to parents and immunisation providers.